Analysing the response of CO2 emissions to business cycle in a developing economy: evidence for South Africa post-apartheid era - Espoir, Delphin Kamanda; Sunge, Regret; Mduduzi, Biyase; Bannor, Frank; Matsvai, Simion (Frontiers in Environmental Science, 2024)
This research addresses the response of CO2 emissions to economic fluctuations in South Africa post-Apartheid, covering the period 1990 to 2018. While previous studies focused on developed countries, limited attention has been given to sub-Saharan developing nations. The study challenges the assumption of constant emissions elasticity in current forecasts and employs a two-step strategy. Firstly, using a rolling-window regression with Hodrick-Prescott filtering, the research finds that the CO2 emissions elasticity varies over time, confirmed through alternative filtering techniques (Christiano-Fitzgerald, Baxter-King, and the Butterworth filter). Secondly, a Markov-switching approach reveals a regime-switching behavior in GDP, indicating negative CO2 emissions elasticity during recessions and positive elasticity during expansions. These findings persist even when accounting for monetary policy shocks and productivity shocks in the Environmental Dynamic Stochastic General Equilibrium (E-DSGE) model. Noteworthy is that South Africa is among the top 20 greenhouse gas emitters globally. The study recommends tailored carbon-pricing policies that are conscious of the countercyclical nature of business cycles. Pricing emissions higher during economic upswings aligns with periods of growth. Additionally, the government is advised to invest in research and development for energy conservation, efficiency, and renewable technologies to counterbalance emissions growth. Implementing emission caps and tax incentives can further enforce pollution abatement measures. Policymakers should consider these asymmetrical responses when addressing global warming challenges in South Africa.